Mechanistic insight into human milk extracellular vesicle‐intestinal barrier interactions - Xiang Luo; Yunyue Zhang; Ning Ding; Jana Javorovic; Bahijja Tolulope Raimi‐Abraham; Steven Lynham; Xiaoping Yang; Natalie Shenker; Driton Vllasaliu (Journal of Extracellular Biology)
Abstract Human milk extracellular vesicles (EVs) are crucial mother‐to‐baby messengers that transfer biological signals. These EVs are reported to survive digestion and transport across the intestine. The mechanisms of interaction between human milk EVs and the intestinal mucosa, including epithelial uptake remain unclear. Here, we studied the interaction of human milk EVs with the gut barrier components, including intestinal biofluids, enzymes, mucus and epithelium. Additionally, we probed the endocytic mechanisms mediating the EV intestinal uptake. Finally, using proteomic analysis, we determined the existence and identification of proteins enriched in the EV fraction transported across the intestinal epithelium. We show that human milk EVs are largely stable in the biochemical gut barriers and demonstrate high mucus diffusivity. EVs show a high level of epithelial cell uptake (∼70%) and efficient transport across Caco‐2 monolayers. Whilst cell uptake of EVs was mediated by multiple routes, none of the pathway‐specific inhibitors inhibited their epithelial translocation. Proteomic analysis of EVs transported across Caco‐2 monolayers identified 14 enriched EV proteins that may facilitate intestinal transport. These findings significantly expand our understanding of the interactions between human milk EVs and the gut barriers, including their intestinal uptake.